Gendered differences in decision-making and participation in value chains: lessons from the highlands of Peru. Issue 4 (19th May 2022) - Tobin, Daniel; Castellanos, Paige
ABSTRACT: Value chain development (VCD) has emerged as one pro-poor market-oriented strategy targeting smallholder farmers. Emphasis has been placed on women smallholders, but few studies examine intra-household dynamics related to VCD opportunities. Through a case study on native potato value chains in the central highlands of Peru, this study draws on semi-structured interviews to explore intra-household decisions to participate in VCD, how household agricultural labour is organised, and barriers to women's involvement. Despite efforts encouraging women to participate, men dominated all aspects of the initiative. Thus, proactive efforts by development organisations need to address resource discrepancies and entrenched gender norms.